Chaya (Cnidoscolus aconitifolius (Mill.) I.M. Johnst) leaf extracts regulate mitochondrial bioenergetics and fatty acid oxidation in C2C12 myotubes and primary hepatocytes. (10th August 2023) - Avila-Nava, Azalia; Acevedo-Carabantes, Joshua Ayork; Alamilla-Martinez, Itzayana; Tobón-Cornejo, Sandra; Torre-Villalvazo, Ivan; Tovar, Armando R.; Torres, Nimbe; Noriega, Lilia G.
Abstract: Ethnopharmacological relevance: Chaya ( Cnidoscolus aconitifolius (Mill.) I.M. Johnst) is an important component of the regular diet and traditional medicine of indigenous communities in Mexico. Customarily, Chaya is consumed as a beverage made of macerated leaf, cooked, or prepared in teas or infusions to empirically treat obesity, diabetes, gastrointestinal disorders, and kidney stones. The beneficial effects of Chaya can be attributed to the presence of protein, dietary fiber, vitamins, and especially polyphenols, which regulate mitochondrial function. Therefore, polyphenols present in Chaya extracts could be used to develop novel strategies to prevent and treat metabolic alterations related to mitochondrial dysfunction in the muscle and liver of subjects with obesity, type 2 diabetes, and cardiovascular diseases. However, limited information is available concerning the effect of Chaya extracts on mitochondrial activity in those tissues. Aim of the study: The aim of this study was to evaluate the antioxidant capacity of an aqueous extract (AE) or mixed (methanol/acetone/water) extract (ME) of Chaya leaf and their effect on C2C12 myotubes and primary hepatocyte mitochondrial bioenergetics and fatty acid oxidation (FAO). Materials and methods: Total polyphenol content and antioxidant activity were determined using the Folin–Ciocalteu method and the oxygen radical absorbance capacity assay, respectively. The effect of AE and ME from Chaya leaf on mitochondrial activity and FAO of C2C12 myotubes and primary hepatocytes was evaluated using an extracellular flux analyzer. Results: The AE and ME from Chaya leaf exhibited antioxidant activity and a polyphenol content similar to nopal, another plant used in Mexican traditional medicine. AE significantly (p < 0.05) decreased the maximal respiration and spare respiratory capacity (SRC) of C2C12 cells, whereas ME had little effect on C2C12 mitochondrial function. Conversely, ME significantly (p < 0.05) decreased SRC in primary hepatocytes, whereas AE increased maximal respiration and SRC at low doses (5 and 10 μM). Moreover, low doses of Chaya AE significantly (p < 0.05) increased AMPK phosphorylation, acyl-coenzyme A oxidase protein abundance, and palmitate oxidation in primary hepatocytes. Conclusion: The AE of Chaya leaf increases mitochondrial function and FAO of primary hepatocytes, indicating its potential to treat hepatic mitochondrial dysfunction underlying metabolic diseases. Graphical abstract: Image 1 Highlights: Chaya leaf aqueous extract has higher antioxidant activity and polyphenols than a mixed extract. Chaya leaf aqueous extract increases mitochondrial function on primary hepatocytes. Chaya leaf aqueous extract increases fatty acid oxidation on primary hepatocytes.